Análisis de las manifestaciones culturales de la parroquia Abañin. - Armijos Becerra, Leydis Maria (My University, 2019)
In the present research work the cultural manifestations of the Abañin parish are approached as an object of study, considering that it is important to keep the heritage alive to contribute to conservation and protection because it is an essential part of the heritage of their ancestors for the customs and traditions that are transmitted to present and future generations. Two objectives were presented in this study, which are: to identify the cultural manifestations that the Parish possesses and to elaborate a proposal for the valuation for the conservation and diffusion of the same ones with the purpose that is oriented to the value of the intangible cultural heritage that owns the parish of Abañin. For the development of the work the descriptive method was used to analyze and describe the object of study, with the application of the research technique such as the survey that allowed to gather information on the use and assessment that the local population has on the object of study. As a result, it can be determined that the Abañin Parish is very rich in terms of cultural manifestations, given the circumstances that are still transmitted to future generations as part of their cultural identity, however, since the governance structure does not manage projects aimed at the protection, promotion and dissemination of cultural events to promote tourism, in order to generate sources of economic income that contribute to the development of the town.
En el presente trabajo de investigación se aborda como objeto de estudio a las manifestaciones culturales de la parroquia de Abañin, considerando que es importante mantener vivo el patrimonio para contribuir con la conservación y protección debido a que forma parte esencial dentro de la herencia de sus antepasados por las costumbres y tradiciones que se transmiten a las generaciones presentes y futuras. Se plantearon dos objetivos en presente estudio, los cuales son: identificar las manifestaciones culturales que posee la Parroquia y elaborar una propuesta para la valorización para la conservación y difusión de las mismas con la finalidad que se oriente a la puesta en valor del patrimonio cultural inmaterial que posee la parroquia de Abañin. Para el desarrollo del trabajo se empleó el método descriptivo para analizar y describir el objeto de estudio, con la aplicación de la técnica de investigación como lo es la encuesta que permitió levantar información sobre uso y valoración que tiene la población local sobre el objeto de estudio. Como resultado se puede determinar que la Parroquia Abañin es muy rica en cuanto a manifestaciones culturales, dada las circunstancias que estas aún se transmiten a las futuras generaciones como parte de su identidad cultural, sin embargo desde la estructura de la gobernanza no gestiona proyectos encaminados a la protección, promoción y difusión de las manifestaciones culturales para promover el turismo, con la finalidad de generar fuentes de ingresos económicos que contribuyan con el desarrollo de la localidad.
Keywords: PATRIMONIO CULTURAL; MANIFESTACIONES; GENERACIONES; TRADICIONES; COSTUMBRES